Efficient Erbium‐Sensitized Core/Shell Nanocrystals for Short Wave Infrared Bioimaging. Issue 20 (26th July 2018) - Wang, Xin; Yakovliev, Artem; Ohulchanskyy, Tymish Y.; Wu, Lina; Zeng, Songjun; Han, Xiaojun; Qu, Junle; Chen, Guanying
Abstract: The 1500–1700 nm spectral range in short wave infrared (SWIR) region allows for biological imaging with large imaging depth, high contrast and resolution. However, very few SWIR imaging probes exist, and rarely reported probes (e.g., rare‐earth‐based ones with excitation at 980 nm) are often associated with biological heating effect. Here, a class of erbium (Er 3+ )‐sensitized core–shell nanocrystals of NaErF4 :Yb 3+ @NaLuF4, which emit efficient SWIR luminescence peaked at 1525 nm under 808 nm excitation, without producing any local heating, is described. The inert shell inhibits concentration‐dependent quenching and allows for an enriched incorporation of 100% Er 3+ into the core, yielding about ≈650‐fold higher SWIR luminescence than parent core nanocrystals. Importantly, an appropriate doping of ytterbium (Yb 3+ ) (optimized concentration, 20%) into the core is shown to further enhance SWIR luminescence (by twofold), endowing the nanocrystals with a high quantum yield of 11%. This Yb 3+ ‐mediated enhancement is possibly due to the suppression of upconverting pathways and the formation of energy trapping centers that prevent the energy migration to intrinsic lattice defects. These bright SWIR core/shell nanocrystals allow high contrast in vitro imaging of HeLa cells and in vivo through‐skull imaging of blood vasculature in the mouse brain. Abstract : The 1500–1700 nm spectral range in short wave infrared (SWIR) region permits biological imaging with large imaging depth, high contrast and resolution. A class of erbium (Er 3+ )‐sensitized core–shell nanocrystals of NaErF4 :Yb 3+ @NaLuF4, emitting efficient SWIR luminescence at 1525 nm under 808 nm excitation, is designed and synthesized, allowing to demonstrate high contrast luminescence bioimaging in vitro and in vivo.